Environmental, sustainability and ecological aspects of cork products for building - Gil, Luís (2012)
This paper summarizes the environmental and ecological aspects, sustainability aspects related to the production and utilization of cork products in the field of building. Cork based products still lack the desired level of information and diffusion within stakeholders in the design and selection of materials for construction, compared with other competing products. However, they potentially offer aspects of sustainability and energy efficiency are in the order of the day. Also considered are green building and sustainable materials which are concepts that are increasingly considered by engineers, architects and other technicians and even by consumers. This paper refers to cork materials for building and their relation with all these concepts.